Pergeseran Motif Budaya Pada Kain Sulaman Karawo Gorontalo - Rumambie, Wira Pratama (Universitas Negeri Gorontalo, 2025)
Gorontalo is the 32nd province located in the northern part of the island of Sulawesi, Indonesia. Gorontalo is known for its rich culture and deep traditions. One of the most famous cultural heritages of Gorontalo is Karawo embroidery fabrics. Karawo is a cloth decorated with intricate hand embroidery, usually used in traditional events or as a symbol of social status. The motifs on Karawo fabric are inspired by nature and the social life of the people of Gorontalo, have high symbolic value and become a distinctive cultural identity. However, along with the times, the motifs on Karawo fabric began to shift. This study aims to analyze the shift in motives, using a qualitative approach strengthened by the theory of the totality principle and the time principle. The principle of totality helps to analyze aspects of function, meaning, and symbolism in Karawo's design, while the principle of time examines the changes that occur in Karawo fabrics based on four indicators: what is fixed, what is lost, what is new, and what is changing. Despite the shift of Karawo motifs towards more modern designs, some Karawo fabrics still retain strong traditional cultural elements. In this study, it was concluded that even though there were changes in the design of the motifs, Karawo fabric still reflected Gorontalo's dynamic cultural identity and was able to adapt to the demands of the times.